1986
DOI: 10.1557/jmr.1986.0685
|View full text |Cite
|
Sign up to set email alerts
|

Cesium and bromine doping into hexagonal boron nitride

Abstract: Using a two-zone method, the possible formation of an intercalation compound of hexagonal boron nitride (BN) with Cs and Br 2 was investigated. Only a few percent weight increase was observed by doping BN with Cs and Br 2 . The electron paramagnetic resonance (EPR) signal was significantly modified by Cs doping, which is attributed to the reaction between the Cs atoms and spin resonance centers (N vacancies) in BN; no change in the EPR spectra was observed with Br 2 doping. However, the deep blue colored Cs-BN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

1999
1999
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…Our calculations show that the BN is highly doped (Figure b), with a carrier concentration of 2 × 10 14 cm –2 , even though the conduction band of planar BN is 2.0 eV above the Fermi level of the electrene. This electron transfer is even more surprising given that prior efforts to dope BN with alkali metals have not succeeded …”
Section: Results and Discussionmentioning
confidence: 99%
“…Our calculations show that the BN is highly doped (Figure b), with a carrier concentration of 2 × 10 14 cm –2 , even though the conduction band of planar BN is 2.0 eV above the Fermi level of the electrene. This electron transfer is even more surprising given that prior efforts to dope BN with alkali metals have not succeeded …”
Section: Results and Discussionmentioning
confidence: 99%
“…Intercalation and its related functions have been widely studied for graphite. In the case of h-BN, intercalation with alkali-metal atoms, [43][44][45] transition-metal atoms, 46 and molecules such as Br 2 ͑Ref. 44͒ and S 2 O 6 F 2 ͑Ref.…”
Section: Isolatedmentioning
confidence: 99%
“…Freeman and Larkindale (4,5) reported that a pink product from the interaction of h-BN with FeCl was accompanied by a small expansion of the interlayer spacing, but Ohashi and Shinjo (6) made an extensive study of this system and concluded that the pink material was due to a surface hydrolysis product, FeOCl. Reductive intercalation of h-BN by alkali metals has also been claimed, (7) but not substantiated (8).…”
Section: Had Claimed a Variety Of Intercalation Compounds Involving mentioning
confidence: 99%
“…[8] Charge carriers with small e!ective mass behave as light, mobile particles, whereas heavy carriers with large e!ective mass have lower mobilities. In general, the charge carrier has a small e!ective mass in wide bands and a large e!ective mass in narrow bands.…”
Section: Conductivity Of (Bn)mentioning
confidence: 99%